Garden — soul mirror - Pawlata, Małgorzata (Lustro, 2020)
Perceiving a garden as a mirror of a soul is the subject taken up by the author in the essay. The writer looks at different conceptions of garden creations from Middle Ages, concentrating on the conceptions of gardens in the age of Enlightenment. The phenomenon of a garden as a mirror of a soul can be analysed with partly architectural and partly philosophical conception of “the memory of gardens” oscillating around three aspects: aesthetics of a garden, philosophy of nature and cosmogony. According to the theory presented in the essay, each garden can be subject to analysis on each level. The author writes about popular in the age of Enlightenment Jean Jacques Rousseau’s beliefs and shows how they have been reflected and how they have evolved in Polish representations of the art of creating gardens.